Neurocognitive impairment in adolescent major depressive disorder: State vs. trait illness markers - Maalouf, Fadi T. (2011)
BACKGROUND: Current treatment outcomes of Major Depressive Disorder (MDD) in adolescents remain suboptimal. Discriminating between state and trait markers of MDD in adolescents would help identify markers that may guide choice of appropriate interventions and help improve longer-term outcome for individuals with the illness. METHODS: We compared neurocognitive performance in executive function, sustained attention and short-term memory in 20 adolescents with MDD in acute episode (MDDa), 20 previously depressed adolescents in remission (MDDr) and 17 healthy control participants (HC). RESULTS: There was a group difference that emerged for executive function with increasing task difficulty (p = 0.033). MDDa showed impaired executive function, as measured by using more moves to solve 4-move problems on a forward planning task, relative to MDDr and HC (p = 0.01, d = 0.94 and p = 0.015, d = 0.77 respectively). MDDa showed more impulsivity as measured by lower response bias (B″) on a sustained attention task than both MDDr and HC (p = 0.01, d = 0.85 and p = 0.008, d = 0.49 respectively). Higher impulsivity was associated with more severe depression (r = −0.365, p = 0.022) and earlier age of onset of depression (r = 0.402, p = 0.012) and there was a trend for a correlation between more executive dysfunction and more severe depression (r = 0.301 p = 0.059) in MDDa and MDDr combined. The three groups did not differ significantly on short-term memory or target detection on the sustained attention task. LIMITATION: These results need to be replicated in the future with a larger sample size. CONCLUSION: Executive dysfunction and impulsivity appear to be state-specific markers of MDD in adolescents that are related to depression severity and not present in remission.